ANALISIS MANFAAT PENGGUNAAN E-MODUL INTERAKTIF SEBAGAI MEDIA PEMBELAJARAN JARAK JAUH DI MASA PANDEMI COVID-19 - Fatika Wulandari; Relsas Yogica; Rahmawati Darussyamsu (Khazanah Pendidikan, 2021)
Interactive e-module is one of the learning media that has many benefits. In this e-module there are features such as text, images, animations and videos that make it easier for students to understand lessons, especially during distance learning. This research was conducted through a literature study method from various literatures such as books, articles from electronic journals, trusted websites and various statistical data sourced from the internet which will then be investigated through several stages which will then be examined through several stages, including: descriptive analysis, content analysis, and critical analysis. Based on the results of research through library research, the use of interactive e-modules can increase students' learning motivation, students' scientific literacy skills, student learning outcomes, students' independence and students' critical thinking skills. From the results of the study, we can see that this e-module can be a choice of learning media that can be used by teachers in distance learning.